Introduction to the Special Issue: Select Papers Presented at the 2019 OLC Accelerate Conference and the 2020 OLC Innovate Conference - Moskal, Patsy (Online Learning, 2020)
We are happy to present five articles selected from the many presented at OLC Accelerate, held November 19-22, 2019 in Orlando, Florida and OLC Innovate, moved from Chicago to a virtual conference in June 15-26, 2020. We invite the readers to consider presenting their research to OLC conferences in the future.